Blood Pressure, Stress Level, and Age with Sleep Quality in Elderly - Nety Mawarda Hatmanti; Yurike Septianingrum; Erika Martining Wardani; Rusdianingseh; Alimatus Sa’diyah (Jurnal Ilmiah Kesehatan, 2024)
The ageing process in the elderly will cause several changes in the life cycle, one of which is in terms of sleep needs. Elderly sleep needs include sleep quality and quantity.